The Fog of War: Eleven Lessons from the Life of Robert S. McNamara - Errol Morris; Robert McNamara (USA Sony Pictures Classics, 2003)
Documentary about Robert McNamara, Secretary of Defense in the Kennedy and Johnson Administrations, who subsequently became president of the World Bank. The documentary will combine an interview with Mr. McNamara discussing some of the tragedies and glories of the 20th Century, archival footage, documents, and an original score by Philip Glass.
A film about the former US Secretary of Defence and the various difficult lessons he learned about the nature and conduct of modern war.
Language: English Subtitles: English, Turkish
Keywords: Biography; Documentary